Changes in the control of skin blood flow with exercise training: where do cutaneous vascular adaptations fit in? - Simmons, G. H.; Wong, B. J.; Holowatz, L. A.; Kenney, W. L. (Experimental Physiology, 2011)
Heat is the most abundant byproduct of cellular metabolism. As such, dynamic exercise in which a significant percentage of muscle mass is engaged generates thermoregulatory demands that are met in part by increases in skin blood flow. Increased skin blood flow during exercise adds to the demands on cardiac output and confers additional circulatory strain beyond that associated with perfusion of active muscle alone. Endurance exercise training results in a number of physiological adaptations which ultimately reduce circulatory strain and shift thermoregulatory control of skin blood flow to higher levels of blood flow for a given core temperature. In addition, exercise training induces peripheral vascular adaptations within the cutaneous microvasculature indicative of enhanced endothelium-dependent vasomotor function. However, it is not currently clear how (or if) these local vascular adaptations contribute to the beneficial changes in thermoregulatory control of skin blood flow following exercise training. The purpose of this Hot Topic Review is to synthesize the literature pertaining to exercise training-mediated changes in cutaneous microvascular reactivity and thermoregulatory control of skin blood flow. In addition, we address mechanisms driving changes in cutaneous microvascular reactivity and thermoregulatory control of skin blood flow, and pose the question: what (if any) is the functional role of increased cutaneous microvascular reactivity following exercise training